Early Use of Inhaled Nitric Oxide in Preterm Infants: Is there a Rationale for Selective Approach? - Chandrasekharan, Praveen; Kozielski, Rafal; Kumar, Vasantha H.S.; Rawat, Munmun; Manja, Veena; Ma, Changxing; Lakshminrusimha, Satyan (American Journal of Perinatology, 2017)
Background Inhaled nitric oxide (iNO) is being increasingly used in preterm infants < 34 weeks with hypoxemic respiratory failure (HRF) and/or pulmonary hypertension (PH).Objective To evaluate the risk factors, survival characteristics, and lung histopathology in preterm infants with PH/HRF.Methods Retrospective chart review was conducted to determine characteristics of 93 preterm infants treated with iNO in the first 28 days and compared with 930 matched controls. Factors associated with survival with preterm HRF and smooth muscle actin from nine autopsies were evaluated.Results Preterm neonates treated with iNO had a higher incidence of preterm prolonged rupture of membrane (pPROM ≥ 18 hours), oligohydramnios and delivered by C-section. In infants treated with iNO, antenatal steroids (odds ratio [OR],3.7; confidence interval [CI], 1.2–11.3; p = 0.02), pPROM (OR, 1.001; CI, 1.0–1.004; p = 0.3), and oxygenation response to iNO (OR, 3.7; CI, 1.08–13.1; p = 0.037) were associated with survival. Thirteen infants with all three characteristics had 100% (13/13) survival without severe intraventricular hemorrhage (IVH)/periventricular leukomalacia (PVL) compared with 48% survival (12/25, p = 0.004) and 16% severe IVH/PVL without any of these factors. Severity of HRF correlated with increased smooth muscle in pulmonary vasculature.Conclusion Preterm infants with HRF exposed to antenatal steroids and pPROM had improved oxygenation with iNO and survival without severe IVH/PVL. Precisely targeting this subset may be beneficial in future trials of iNO.
Keywords: inhaled nitric oxide; hypoxemic respiratory failure; preterm prolonged rupture of membrane; pulmonary hypertension; smooth muscle area ratio